Ti3C2Tx hollow microsphere as well as preparation method and application thereof
By making MXene material into Ti3C2Tx hollow microspheres, the existing MXene material lacks performance when adsorbing tetracycline and macrolide antibiotics, achieving efficient and stable antibiotic adsorption effect.
Patent Information
- Application Number
- CN202510041272.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-03-28
AI Technical Summary
When the existing MXene materials adsorb tetracycline and macrolide antibiotics in water, their adsorption performance is insufficient and cannot meet the actual application needs.
By making the MXene material into Ti3C2Tx hollow microspheres, the single layer of Ti3C2Tx dispersion is used to electrostatically self-assemble with the PS spheres to form a core-shell structure of Ti3C2Tx hollow microspheres.
It improves the ability to adsorb tetracycline and macrolide antibiotics, has faster adsorption kinetics, higher removal efficiency and adsorption capacity, and has high physical and chemical stability and strong anti-fouling properties.
Smart Images

Figure CN119701859A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorption material preparation, and in particular to a Ti3C2T x Hollow microspheres and preparation methods and applications thereof. Background Art
[0002] Antibiotics, as a type of new pollutants, are widely used in the prevention and treatment of diseases in humans, animals and plants because they can effectively fight bacterial infections. Antibiotics used in aquaculture can enter the aquatic environment through the discharge of aquaculture wastewater and soil infiltration, leading to the production of drug-resistant bacteria, increasing the risk of disease transmission, and harming the ecosystem while also producing a new pollutant. Therefore, the treatment of antibiotics in aquaculture wastewater is of great significance for environmental protection and public health. Since conventional wastewater treatment cannot effectively eliminate antibiotics, researchers at home and abroad have developed a variety of technologies to treat antibiotics in wastewater. These technologies include both physical / chemical methods, such as coagulation, adsorption, membrane filtration, advanced oxidation processes (AOPs) and ion exchange, as well as biological treatments, such as activated sludge, trickling filtration and artificial wetlands. However, most of the above methods have disadvantages such as incomplete impurity removal, high energy consumption, production of toxic sludge and complex operating procedures. Adsorption separation has the advantages of high cost-effectiveness, simple operation and strong practicality, and has been widely studied and applied.
[0003] For aquaculture wastewater with complex components, the adsorbent is easily affected by the phase and polarity of pollutants in this open field, and cannot be in close contact with pollutant molecules, resulting in low adsorption efficiency of the adsorbent. Porous hollow spheres have rich pore structures and high specific surface areas, which can provide abundant inner and outer double-layer adsorption sites. In addition, the cavity structure inside the hollow sphere can promote fluid flow, reduce diffusion resistance, and thus improve the mass transfer process. Good adsorbents have super strong adsorption capacity and reusability, and can adsorb a large amount of pollutants. The most common adsorbents are composed of natural or synthetic materials, such as carbon-based materials, nanomaterials, biomass materials, polymer materials, etc. However, the reported adsorbents are unstable, have small specific surface areas, are difficult to synthesize, have complex implementation procedures, and have poor adsorption capacity, which seriously restricts their practical application. MXene has the characteristics of controllable pore structure, adjustable chemical composition, high specific surface area, and physicochemical stability. It is considered to be a very promising adsorbent for wastewater treatment. However, due to the existence of van der Waals forces between MXene flakes, MXene is prone to self-stacking, resulting in insufficient pore structure as an adsorbent material and the inability to provide abundant active sites. As a result, the performance of adsorbing antibiotics in water still cannot meet the requirement of 80 mg of antibiotics per 1 gram of adsorbent, which restricts the use of MXene materials as antibiotic adsorbent materials.
[0004] In summary, there is an urgent need to provide a MXene material with rich pore structure and active sites, thus having excellent antibiotic adsorption performance. Summary of the invention
[0005] The present invention aims to provide a MXene material with a hollow spherical structure, thereby increasing the specific surface area, providing abundant sites, promoting fluid flow, reducing diffusion resistance, thereby improving the mass transfer process, and solving the problem of increasing the adsorption of tetracyclines and macrolide antibiotics in wastewater.
[0006] In order to achieve the above-mentioned object, the present invention firstly provides a Ti3C2T x A method for preparing hollow microspheres, wherein the preparation method comprises:
[0007] S1: Add LiF to HCl solution, stir until LiF is dissolved, add Ti3AlC2, etch, centrifuge, wash, sonicate, centrifuge for the second time to obtain a single layer Ti3C2T x Dispersion liquid;
[0008] S2: The single-layer Ti3C2T obtained in S1 x The dispersion and PS beads were stirred for the second time, filtered, dried, and calcined to obtain Ti3C2T x Hollow microspheres;
[0009] Among them, S2, Ti3C2T x The mass ratio with PS beads is 1:3-7;
[0010] Wherein, in S2, the second stirring conditions include: the second stirring temperature is 20-30° C., and the second stirring time is 12-48 h.
[0011] The second aspect of the present invention provides a Ti3C2T prepared by the above preparation method. x Hollow microspheres.
[0012] The third aspect of the present invention provides the Ti3C2T x Application of hollow microspheres in the adsorption of tetracyclines and macrolide antibiotics.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] Ti3C2T prepared by the preparation method provided by the present invention x Hollow microspheres can effectively adsorb tetracyclines and macrolide antibiotics in solutions, have faster adsorption kinetics, higher removal efficiency and adsorption capacity, have high physicochemical stability and strong anti-fouling properties, and have certain application prospects in the treatment of actual wastewater containing antibiotics. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The single-layer Ti3C2T x TEM;
[0016] Figure 2 The Ti3C2T prepared in Example 1 x SEM of hollow microspheres;
[0017] Figure 3 The Ti3C2T prepared in Example 1 x TEM of hollow microspheres
[0018] Figure 4 It is a single layer Ti3C2T x , PS balls, PS@Ti3C2T x 、Ti3C2T x TG graph of hollow microspheres;
[0019] Figure 5 The Ti3C2T prepared in Example 1 x Curve of the adsorption amount of tetracycline and macrolide antibiotics by hollow microspheres changing with time;
[0020] Figure 6 The Ti3C2T prepared in Example 1 x Pseudo-first-order kinetic equations for the adsorption of tetracyclines and macrolide antibiotics onto hollow microspheres;
[0021] Figure 7 The Ti3C2T prepared in Example 1 x Adsorption of tetracyclines and macrolide antibiotics by hollow microspheres under different pH conditions. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] MXene has the characteristics of controllable pore structure, adjustable chemical composition, high specific surface area, and physicochemical stability, and is considered to be a promising adsorbent for wastewater treatment.
[0024] However, if only MXene materials are used, the adsorption performance can be improved, but it is still not enough to achieve effective adsorption of tetracyclines and macrolide antibiotics. The existing technology uses intercalation method to prepare lamellar MXene materials, but it still cannot significantly improve the adsorption performance of materials for antibiotics. Therefore, although MXene materials have the above advantages, the existing adsorption capacity for tetracyclines and macrolide antibiotics hinders its application in the adsorption of tetracycline antibiotics and macrolide antibiotics in wastewater.
[0025] Only by providing more adsorption sites on MXene materials and improving the mass transfer process can the adsorption performance of tetracycline antibiotics and macrolide antibiotics in wastewater be effectively improved. To achieve this goal, the inventors tried to explore how to provide more adsorption sites on MXene materials and improve the mass transfer process. In order to further effectively improve the adsorption performance of tetracycline antibiotics and macrolide antibiotics in wastewater by MXene materials, the inventors unexpectedly discovered that the above purpose can be achieved by making MXene materials into hollow microspheres.
[0026] To this end, the first aspect of the present invention provides a Ti3C2T x A method for preparing hollow microspheres, wherein the preparation method comprises:
[0027] S1: Add LiF to HCl solution, stir until LiF is dissolved, add Ti3AlC2, etch, centrifuge, wash, sonicate, centrifuge for the second time to obtain a single layer Ti3C2T x Dispersion liquid;
[0028] S2: The single-layer Ti3C2T obtained in S1 x The dispersion and PS beads were stirred for the second time, filtered, dried, and calcined to obtain Ti3C2T x Hollow microspheres;
[0029] Among them, S2, Ti3C2T x The mass ratio with PS beads is 1:3-7;
[0030] Wherein, in S2, the second stirring conditions include: the second stirring temperature is 20-30° C., and the second stirring time is 12-48 h.
[0031] In the present invention, a single layer Ti3C2T x Preparation method of mixing dispersion and PS beads, making Ti3C2T x The sheet wraps around the PS ball to form a core-shell structure. In S2, the above-mentioned specific Ti3C2T x The mass ratio of Ti3C2T xThe shell of Ti3C2T is completely spherical and does not produce multi-layer stacking. x If the dosage is too large, the PS beads will be wrapped with more sheets, resulting in stacking and reducing the adsorption active sites. If the dosage of PS beads is too large, the sheets will not completely wrap the beads, forming spherical cavities and unable to become complete spheres.
[0032] According to the present invention, the concentration of the HCl solution is 9-12M, and the dosage ratio of LiF to HCl solution is 1g:
[0033] 9.5-12.5 mL, the mass ratio of LiF to Ti3AlC2 is 0.9-2.0:1.
[0034] According to the present invention, in S1, the first stirring condition includes: a stirring rate of 300-800 r / min.
[0035] According to the present invention, in S1, the etching conditions include: etching temperature of 40-50° C., and etching time of 24-48 h.
[0036] According to the present invention, in S1, the conditions of the first centrifugation include: a first centrifugation speed of 2000-5000 r / min, and a first centrifugation time of 5-10 min.
[0037] According to the present invention, the washing conditions include: washing 3-5 times with a dilute hydrochloric acid solution.
[0038] According to the present invention, in S1, the conditions of the second centrifugation include: the second centrifugation speed is 2000-5000 r / min, and the second centrifugation time is 10-60 min.
[0039] According to the present invention, in S1, the ultrasonic conditions include: under a nitrogen atmosphere, an ultrasonic power of 200-350 W, and an ultrasonic time of 1-3 h.
[0040] According to the present invention, in S2, the particle size of the PS beads is 0.5-5 μm, and the single-layer Ti3C2T x Dispersion of Ti3C2T x The concentration is 1.5-5.5g / L.
[0041] According to some embodiments of the present invention, preferably, the particle size of the PS beads is 0.5-1.5 μm.
[0042] In the present invention, the nano-sized PS beads used in the prior art will make Ti3C2T x The sheet cannot completely wrap the PS beads due to its own rigid structure. The PS beads with the above specific particle size range are selected to make Ti3C2Tx The sheet can completely wrap the PS ball. If the particle size of the PS ball is too large, multi-layer wrapping and partial wrapping will be formed under the same mass condition. If the particle size of the PS ball is too small, a Ti3C2T x The sheets cannot form complete hollow microspheres.
[0043] According to the present invention, in S2, the filtering condition is negative pressure filtration using a 0.22 μm microporous filter membrane.
[0044] According to the present invention, in S2, the drying conditions include: vacuum drying, a drying temperature of 35-45° C., and a drying time of 6-12 h.
[0045] According to the present invention, the calcination conditions include: under nitrogen protection, the calcination temperature is 350-550° C., and the calcination time is 20-60 min.
[0046] The second aspect of the present invention provides a Ti3C2T prepared by the above preparation method. x Hollow microspheres.
[0047] The third aspect of the present invention provides the Ti3C2T x Application of hollow microspheres in the adsorption of tetracyclines and macrolide antibiotics.
[0048] The present invention will be described in detail below through examples.
[0049] Test description:
[0050] Ti3C2T x The method for determining the adsorption amount of the hollow microspheres is as follows: 100 mg / L tetracycline solution and tylosin tartrate solution are respectively prepared as stock solutions, and the stock solutions are diluted step by step to obtain standard solutions of a series of concentrations (1, 2, 5, 8, 10, 15, 20, 30, 40, 50 mg / mL). The maximum absorption wavelengths of tetracycline and tylosin tartrate are measured on a UV-visible spectrophotometer. The absorbance A of each concentration is measured at the maximum absorption wavelength. With the concentration C (mg / mL) as the abscissa and the absorbance A as the ordinate, linear regression is performed to obtain the standard curves and linear regression equations of the two antibiotics.
[0051] Add 25 mL of 100 mg / L tetracycline solution to a conical flask and add Ti3C2T x The hollow microspheres were fixed in a constant temperature water bath oscillator to avoid light and oscillated at 25°C for adsorption. Samples were taken at intervals and the absorbance was measured to calculate the Ti3C2T x Adsorption capacity of tetracycline tylosin tartrate by hollow microsphere adsorption material.
[0052] Add 25 mL of 100 mg / L tylosin tartrate into a conical flask and add Ti3C2T x The hollow microspheres were fixed in a constant temperature water bath oscillator to avoid light and oscillated at 25°C for adsorption. Samples were taken at intervals and the absorbance was measured to calculate the Ti3C2T x Adsorption capacity of tetracycline tylosin tartrate by hollow microspheres.
[0053] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.
[0054] Example 1
[0055] S1: Take a clean plastic beaker, add 20mL of 12M HCl, then add 1.6g LiF, start stirring, the speed is 700r / min, stir for 10min to fully dissolve LiF. Slowly add 1.0g Ti3AlC2 to the above solution. The etching temperature is 40℃, and the etching is 24h. After the reaction is completed, centrifuge the sample at 3500r / min for 10min. After the centrifugation, pour out the original etchant, add 1M dilute HCl, and wash with dilute hydrochloric acid 3 times. At this time, the supernatant is a clear colorless solution. Wash with deionized water at 3500r / min, and use 10000r / min when it starts to become turbid until PH>6, and collect the precipitate. Add an appropriate volume of deionized water to the precipitate, pass nitrogen, and ultrasonicate at a power of 240w for 2h. After ultrasonication, centrifuge at a speed of 3500r / min. Collect the upper liquid after 30min to obtain a single layer of Ti3C2T x Dispersion.
[0056] S2: 0.28 g of PS beads with a particle size of 1 μm were mixed with 23 mL of 3 g / L Ti3C2T x Dispersion mixing, Ti3C2T x The mass ratio of the PS beads was 1:4, and the mixture was vigorously stirred at 25 °C for 24 h. Then, the mixture was filtered with a 0.22 μm polytetrafluoroethylene membrane and dried at 60 °C for 6 h to obtain PS@Ti3C2T x Core-shell structure, PS@Ti3C2T x Calcination at 450 °C for 20 min in a nitrogen atmosphere, removal of PS balls, and Ti3C2T x Hollow microsphere A1.
[0057] Example 2
[0058] The preparation method of Example 1 is the same as that of S2, except that Ti3C2T xThe mass ratio of Ti3C2T to PS beads was 1:5. x Hollow microspheres A2.
[0059] Example 3
[0060] The preparation method of Example 1 was followed, except that in S2, the stirring time was 12 h to obtain Ti3C2T x Hollow microsphere A3.
[0061] Example 4
[0062] The preparation method of Example 1 was followed, except that in S2, the particle size of the PS beads was 0.5 μm, and Ti3C2T x Hollow microsphere A4.
[0063] Example 5
[0064] The preparation method of Example 1 was followed, except that in S2, the particle size of the PS beads was 1.5 μm, and Ti3C2T x Hollow microsphere A5.
[0065] Example 6
[0066] The preparation method of Example 1 was followed, except that in S2, the particle size of the PS beads was 3 μm, and Ti3C2T x Hollow microsphere A6.
[0067] Example 7
[0068] The preparation method of Example 1 was followed, except that in S2, the particle size of the PS beads was 5 μm, and Ti3C2T x Hollow microsphere A7.
[0069] Comparative Example 1
[0070] S1: Prepare 20mL of 9mol / L hydrochloric acid solution, then transfer it to a polytetrafluoroethylene container, slowly add 1.6g of lithium fluoride (LiF), stir for 30min with a water bath magnetic stirrer until completely dissolved, set the temperature to 35°C and the speed to 400rpm to obtain a mixed solution of HCl and LiF. Weigh 1g of Ti3AlC2 MAX precursor powder into the above-mentioned mixed solution of HCl and LiF, and add it slowly to avoid overheating. After stirring and etching at 35°C for 24h, collect the product and finally obtain a multilayer Ti3C2MXene dispersion.
[0071] S2: The multilayer Ti3C2MXene dispersion after etching in S1 was centrifuged and washed with a certain amount of 12M hydrochloric acid at 8000rpm for 10 minutes, then the supernatant was removed and the acid washing was repeated three times. The obtained precipitate was then repeatedly centrifuged and washed with deionized water for 10 minutes each time at 8000rpm until the pH value of the supernatant reached neutrality, the centrifugation was stopped, the supernatant was poured out, and the swollen clay-like precipitate in the lower layer was collected and dispersed in a certain amount of deionized water. An ultrasonic cell crusher (300W) was used for ice bath ultrasonication for 30 minutes, and then the ultrasonicated solution was centrifuged at 3500rpm for 15 minutes, and the upper dark green colloidal solution was taken and stored in a dark environment of 4-8°C. 0.28g of PS beads with a particle size of 1μm were mixed with 23mL of 3g / LTi3C2T x The colloids were mixed and stirred vigorously at 25 °C for 24 h, then the mixture was filtered through a 0.22 μm polytetrafluoroethylene membrane and dried at 60 °C for 6 h to obtain PS@Ti3C2T x Core-shell structure, PS@Ti3C2T x Calcination at 450 °C for 20 min in a nitrogen atmosphere, removal of PS balls, and Ti3C2T x Hollow microspheres DA1.
[0072] Comparative Example 2
[0073] The preparation method of Example 1 is the same as that of S2, except that Ti3C2T x The mass ratio of Ti3C2T to PS beads was 1:2.5. x Hollow microspheres DA2.
[0074] Comparative Example 3
[0075] The preparation method of Example 1 is the same as that of S2, except that Ti3C2T x The mass ratio of Ti3C2T to PS beads was 1:7.5. x Hollow microspheres DA3.
[0076] Comparative Example 4
[0077] The preparation method of Example 1 was followed, except that in S2, the particle size of the PS beads was 0.4 μm, and Ti3C2T x Hollow microspheres DA4.
[0078] Comparative Example 5
[0079] The preparation method of Example 1 was followed, except that in S2, the particle size of the PS beads was 5.5 μm, and Ti3C2T x Hollow microspheres DA5.
[0080] A1-A7 and DA1-DA5 were tested for the adsorption of tetracycline and tylosin tartrate, and the results are shown in Table 1.
[0081] Table 1
[0082]
[0083] The adsorption amounts of tetracycline and tylosin tartrate in Table 1 are the adsorption amounts at 300 min.
[0084] It can be seen from Table 1 that the Ti3C2T x The adsorption capacity of the hollow microspheres is better than that of the materials in the comparative example, indicating that the materials provided by the present invention can improve the adsorption performance of tetracycline antibiotics and macrolide antibiotics in wastewater.
[0085] Depend on Figure 1 It can be seen that S1 of Example 1 successfully prepared Ti3C2T x .
[0086] Depend on Figure 2 and Figure 3 It can be seen that the Ti3C2T prepared in Example 1 x It is in the shape of hollow microspheres.
[0087] Depend on Figure 4 It can be seen that in Example 1, after calcination at 450 °C, PS was completely removed and the hollow sphere structure was only Ti3C2T x Ti3C2T x At 800℃, the quality hardly changes, and it has high thermal stability. Figure 4 In the right figure, Ti3C2T x Hollow sphere and Ti3C2T x The curves overlap, indicating that Ti3C2T x The PS in the hollow spheres was completely removed.
[0088] Depend on Figure 5 It can be seen that the Ti3C2T x The hollow microspheres have excellent adsorption capacity for tetracyclines and macrolide antibiotics.
[0089] Depend on Figure 6 It can be seen that the Ti3C2T x The hollow microspheres have fast adsorption kinetics for tetracyclines and macrolide antibiotics.
[0090] Depend on Figure 7 It can be seen that the Ti3C2T x The hollow microspheres still have a high adsorption capacity in extremely acidic and alkaline environments, indicating that the Ti3C2Tx Hollow microspheres have high chemical stability.
[0091] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A Ti3C2T x The method for preparing hollow microspheres is characterized in that: The preparation method comprises: S1: Add LiF to HCl solution, stir until LiF is dissolved, add Ti3AlC2, etch, centrifuge, wash, sonicate, centrifuge for the second time to obtain a single layer Ti3C2T x Dispersion liquid; S2: The single-layer Ti3C2T obtained in S1 x The dispersion and PS beads were stirred for a second time, filtered, dried, and calcined to obtain Ti3C2T x Hollow microspheres; Among them, S2, Ti3C2T x The mass ratio with PS beads is 1:3-7; Wherein, in S2, the second stirring conditions include: the second stirring temperature is 20-30° C., and the second stirring time is 12-48 h.
2. The preparation method according to claim 1, characterized in that: In S1, the concentration of the HCl solution is 9-12M, the usage ratio of LiF to the HCl solution is 1g:9.5-12.5mL, and the mass ratio of LiF to Ti3AlC2 is 0.9-2.0:
1.
3. The preparation method according to claim 1, characterized in that: In S1, the first stirring condition includes: a stirring rate of 300-800 r / min.
4. The preparation method according to claim 1, characterized in that: In S1, the etching conditions include: etching temperature of 40-50°C and etching time of 24-48h.
5. The preparation method according to claim 1, characterized in that: In S1, the conditions of the first centrifugation include: a first centrifugation speed of 2000-5000 r / min, and a first centrifugation time of 5-10 min; The washing conditions include: washing 3-5 times with a dilute hydrochloric acid solution; The conditions of the second centrifugation include: the second centrifugation speed is 2000-5000 r / min, and the second centrifugation time is 10-60 min.
6. The preparation method according to claim 1, characterized in that: In S1, the ultrasonic conditions include: under nitrogen atmosphere, ultrasonic power is 200-350W, and ultrasonic time is 1-3h.
7. The preparation method according to claim 1, characterized in that: In S2, the particle size of the PS beads is 0.5-5 μm, preferably 0.5-1.5 μm, and the single-layer Ti3C2T x Dispersion of Ti3C2T x The concentration is 1.5-5.5g / L.
8. The preparation method according to claim 1, characterized in that: In S2, the filtering condition is to use a 0.22 μm microporous filter membrane under negative pressure; The drying conditions include: vacuum drying, drying temperature of 35-45°C, and drying time of 6-12h; The calcination conditions include: under nitrogen protection, a calcination temperature of 350-550° C., and a calcination time of 20-60 min.
9. A Ti3C2T prepared by the preparation method according to any one of claims 1 to 8 x Hollow microspheres.
10. Ti3C2T as claimed in claim 9 x Application of hollow microspheres in the adsorption of tetracyclines and macrolide antibiotics.